Embalagens de medicamentos: diretrizes para o desenvolvimento - Lucio, Cristina do Carmo [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The medidines are essential in the heath system, with great economic and social importance. Considering the increase in the consumption of medicines in the world, being the Brazil one of the top ten pharmaceutical markets, and the increase in the elderly populaition, its primary user, it is important to know the interface aspects of these packages, as well as understand the aging process and skills and difficulties in handling of their target. There are many of these packages, and many have several problems, from low readability, security issues, which is exarcebated when they are used by the elderly or people with poor manual dexterity or with health problems such as rheumatoid-arthritis. This research aims to generate parameters for regulation and practical application in the packaging industry of medicines and, therefore, were required several theoretical and market research, to understand the interface aspects of these products with their users. Thereby, initially it's presents a comprehensive review of the literature, which includes skills and difficulties in handling products for different users, with emphasis on the elderly, as well as indispensable elements for setting the packaging for medicines, as medicines with interface structural materials, standards, laws and regulations dealing with medicines. To confirm the hypothesis that there are problems at the interface of these packages, the methodologies and the results analysed and discussed the approaches with users, as well as the usability evaluation. After all the data analyzed and discussed in the literature, it was possible to set parameters for the development of new packaging, among them, the ampaule, the tube of ointment, the child protection packaging, the drapper, battles for syrup and bottles for pills and the secondary packaging

Os medicamentos são fundamentais no sistema de saúde, com grande peso econômico e social. Considerando o aumento no consumo de maneira global, sendo o Brasil um dos dez principais mercados farmacêuticos, e ao aumento da população idosa, seu principal usuário, torna-se importante conhecer os aspectos da interface de suas embalagens, bem como entender o processo de envelhecimento e habilidades e dificuldades no manuseio por seus públicos diversos. Há uma infinidade destas embalagens, e muitas apresentam inúmeros problemas, desde baixa legibilidade, a questões relacionadas à segurança, o que é agravado quando são utilizadas por idosos ou pessoas com baixa destreza manual ou ainda com problemas de saúde, como artrite-reumatoide. Esta pesquisa teve por objetivo gerar parâmetros para regulamentação e aplicação prática na indústria de medicamentos e, para tanto, foram necessárias diversas pesquisas, teóricas e de mercado, visando entender os aspectos da interface destes produtos com seus usuários. Desse modo, inicialmente é apresentada uma ampla revisao da literatura, que inclui habilidades e dificuldades na manipulação de produtos por usuários diversos, com ênfase nos idosos, além de elementos indispensáveis para configuração de embalagens para medicamentos, como interface com materiais estruturais, normais, leis e regulamentos específicos. Para confirmar a hipótese de que há problemas de interface, são apresentadas as metodologias e resultados analisados e discutidos das abordagens com os usuários, bem como da avaliação de usabilidade desenvolvida. A partir dos dados analisados e discutidos com base na literatura, foi possível expor parâmetros para o desenvolvimento de novas embalagens, dentre elas, a ampola, a bisnaga, as EEPC (embalagens especiais de proteção à criança), o flaconete, o fraco conta-gotas, o frasco para xarope, o frasco para comprimidos e a embalagem secundária.
Keywords: Desenho industrial; Medicamentos - Embalagens; Ergonomia; Design centrado no usuário; Envelhecimento; Aptidão; Industrial design